2013
DOI: 10.1371/journal.pntd.0002302
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity in Snakebite—The Limits of Our Knowledge

Abstract: Snakebite is classified by the WHO as a neglected tropical disease. Envenoming is a significant public health problem in tropical and subtropical regions. Neurotoxicity is a key feature of some envenomings, and there are many unanswered questions regarding this manifestation. Acute neuromuscular weakness with respiratory involvement is the most clinically important neurotoxic effect. Data is limited on the many other acute neurotoxic manifestations, and especially delayed neurotoxicity. Symptom evolution and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
174
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(185 citation statements)
references
References 209 publications
(297 reference statements)
0
174
0
11
Order By: Relevance
“…In contrast, pre-synaptic neurotoxins are important in human envenoming11, as well as toxins that cause coagulopathy, myotoxicity and nephrotoxicity. For example, a recent study has demonstrated that rodent plasma is highly resistant to procoagulant toxins that are highly relevant for human envenoming12.…”
mentioning
confidence: 99%
“…In contrast, pre-synaptic neurotoxins are important in human envenoming11, as well as toxins that cause coagulopathy, myotoxicity and nephrotoxicity. For example, a recent study has demonstrated that rodent plasma is highly resistant to procoagulant toxins that are highly relevant for human envenoming12.…”
mentioning
confidence: 99%
“…sPLA2s are also some of the most pharmacologically active, multi-effect (neuro-myo-cyto-hemotoxic) venom components ( While sPLA2 inhibition might prove sufficient as a "bridge-to-survival" for many types of venoms when administered in a pre-referral setting and, at times, be sufficient for treatment, future SMTs might be mixtures of other SMT (Figure 3a). Some targets could also be inhibited indirectly by SMTs, such as three-finger toxins, whose effects might sometimes be mitigated by acetylcholinesterase inhibitors, though the use of these inhibitors remains controversial despite decades of use for this purpose [52,61,[64][65][66]. In addition, SMTs might be used to slow the spread of venom by paralyzing lymphatic smooth muscles (e.g., with lignocaine) [67].…”
Section: Venom Target Selectionmentioning
confidence: 99%
“…In 1972, Banerjee et al presented an early example of repurposing an SMT for snakebite when neostigmine was used to treat the paralytic effects of an elapid bite [52]. Multiple groups have since investigated the use of this class of acetylcholinesterase inhibitors in the clinical setting with variable results [52,61,65,66]. Development of a hypothetical SMT using a repurposing pathway are shown in Figure 4.…”
Section: Repurposing As a Strategy For Discovery And Developmentmentioning
confidence: 99%
“…Three patterns of neuromuscular transmission failures have been observed in the neurophysiological studies in these patients: [5,7,8] • Postsynaptic reversible neuromuscular blockade (Cobra spp. -Naja-naja, Naja-nigricollis, Naja-haje) • Postsynaptic irreversible blockade -alpha-bungarotoxin • Presynaptic blockade with inhibition of release of acetylcholine -Beta-and gamma-bungarotoxin, phospholipase A2 activity, viperotoxin F.…”
mentioning
confidence: 95%
“…(Crotoxin, Mojave toxin). [5] The peripheral neuromuscular weakness after a snakebite results from a defective neuromuscular junction (NMJ) transmission. Traditionally, it has been considered that snake venom toxins cause two types of neuromuscular blockade, presynaptic and postsynaptic; but this view may be oversimplistic and needs to be reviewed in view of the recent insights into neuromuscular transmission and descriptions of different patterns of neurotoxicity.…”
mentioning
confidence: 99%